Effectiveness Of Techno Marketing Tools For The Growth Of Pharmaceutical Companies (Journal of Pharmaceutical Negative Results, 2022)
Techno-marketing is a unique combination of technology + Marketing. Techno-marketing is a new disruptive way of marketing which is going to change the future of traditional marketing by using technology. It is the effective way to promote a company's products and services. By this, companies can attract their customers and easily interact with them. Technology is the backbone of all the market strategies around the globe. It provides a short time solution to solve complex marketing problems in today's competitive environment. In this paper, we have focused on Techno-marketing techniques such as Technology Marketing Mix (TM mix), Web 2.0, Cloud computing, Mobile computing and Electronic commerce which are commonly used by many companies in India for their promotional activities in the Indian market. As per the findings of the study, out of all Techno-marketing tools, Web 2.0, Mobile computing and Electronic commerce are the most commonly used by pharmaceutical companies. These technologies are fast catching up and have the potential to increase the sales of top global companies in future. It is also recommended that a company should promote its products using Techno-marketing Tools such as Web 2.0, Mobile computing and e-commerce which can be positively effective in Indian market. The study is based on a sample size of 103 retailers representing 8 top global companies in India.